Comparative assessment of several rainfall erosivity indices in southern Nigeria: short communication - Salako, F.K.; Obi, M.E.; Lal, R. (Elsevier, 1991)
Soil erosion, measured in field runoff plots, was correlated with several rainfall erosivity indices. Erosion was measured on field plots established on a Typic Paleudult in southeastern Nigeria. Several erosivity indices were computed from a daily recording rain gauge sited in vicinity of the runoff plots. Erosivity indices computed included EI30 (WISCHMEIER & SMITH 1978), KE>1 (HUDSON 1971) and AIm (LAL 1976). In addition, several new indices were computed including EkIm and EkI30, where, the new kinetic energy (Ek) factor was computed using an empirical relation developed by KOWAL & KASSAM (1976) in northern Nigeria. Two new indices were slightly better correlated with soil erosion than the conventionally used indices.